Determination of initiating and critical stress levels in compressed plain and high-strength concrete by acoustic methods - J. HOŁA (Archives of Acoustics)
New criteria suitable for determining the levels of initiating stress σi and critical stress σcr in plain and high-strength concrete under compression by acoustic materials testing methods have been established. Also the criteria known from the literature on the subject have been verified. On the basis of the author's own research results obtained by the ultrasonic method and the acoustic emission (AE) method the limits of the applicability of the two above methods have been determined. The new criteria, classified according to their suitability for plain concrete or high-strength concrete, have been defined using such descriptors as: the velocity of longitudinal ultrasonic waves, AE counts, the rate of AE counts, the energy of short AE impulses and the RMS value of AE.